IMPLEMENTASI PERATURAN DAERAH KOTA DUMAI NOMOR 3 TAHUN 2021 TENTANG PENGELOLAAN SAMPAH DI KOTA DUMAI - Neri Anggela; Gusliana HB; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The problem of waste in Dumai City is still a problem, the largepopulation, limited land use and high levels of consumtion have an impact on thecleanliness and beauty of the environment which results in accumulation of wastein various corners of the city. This solid waste problem continues to increase asthe population increases. The existence of the Dumai City Regional Number 3 of2021 concerning Waste Management is a form of Dumai City goverment’s effortto show its seriousness in managing rubbish.This study aims to determine the implementation of the Dumai CityRegional Regulation Number 3 of 2021 concerning Waste Management in theCity of Dumai, the inhibiting factors in the implementation of the Dumai CityRegional Regulation Number 3 of 2021 concerning Waste Management in theCity of Dumai and the effort to implement the Dumai City Regional RegulationNumber 3 of 2021 concerning Waste Management in the City of Dumai.This study uses the type of Sosiological Law research with an approach tofield research techniques, interviews and literature studies. This research wasconducted in Dumai City. The data sources used are primary data sources andsecondary data.The result of this study concluted that the implementation of Dumai CityRegional Regulation Number 3 of 2021 concerning Waste Management in DumaiCity applies a collection and transport system that only emphasizes finalprocessing. The lack of budget result in a shortage of cleaning workers andinadequate infrasturcture in waste management as well as low public awarenessof waste disposal in its place and a lack of firmness in applaying sansctiom.Keywords: Implementation, Regional Regulation, Management, Rubbish.